An EXTERNAL AND INTERNAL FACTORS, HAS AN IMPACT ON MSME PERFORMANCE? - MRN Irawan; S Sutinem; Iva Milatul Chanifah (Universitas 17 Agustus 1945 Surabaya, 2022)
The aims of this study are (1) to analysed external factors consisting of aspects of government policies, aspects of the role of related institutions, social, cultural, and economic aspects of the performance of Micro, Small and Medium Enterprises (MSMEs); (2) analysed internal factors consisting of aspects of Human Resources (HR), financial aspects, technical and operational aspects, as well as market and marketing aspects in the performance of Micro, Small and Medium Enterprises (MSMEs). The data collection method uses a questionnaire, the research sample is 250 MSME business actors registered at the Sidoarjo Regency Trade Office who’s member of the WhatsApp group. The data collection technique is by distributing online questionnaires through the WhatsApp group. Data analysis using SEM with smart PLS 3.0 application. The results showed that there was a significant and positive influence of external factors on the performance of MSMEs; there is a significant and positive influence of internal factors on the performance of MSMEs Keywords: External factors, Internal factors, MSME performance